2022
DOI: 10.3390/ijerph19084525
|View full text |Cite
|
Sign up to set email alerts
|

How Do Older Adults Process Icons in Visual Search Tasks? The Combined Effects of Icon Type and Cognitive Aging

Abstract: Considering the differences in cognitive aging among older adults, this study examined how older adults process different types of graphic icons in visual search tasks. Fifty-four medical-related icons, including flat icons (FIs), FIs plus text (FIs + text), skeuomorphic icons (SIs), and SIs plus text (SIs + text), were created. The participants were divided into two groups—cognitively normal (CN) and mild cognitive impairment (MCI)—to complete a visual search task. According to the eye-tracking data of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Despite the critical role icons play in guiding users, providing instructions, and facilitating task completion [2], previous icon designs have often neglected the needs of visually impaired users. This oversight has led to diminished cognitive effectiveness, disrupted workflows, and potential malfunctions [3][4][5]. A clear and concise icon is imperative for ensuring users accurately interpret its meaning and intended function [6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the critical role icons play in guiding users, providing instructions, and facilitating task completion [2], previous icon designs have often neglected the needs of visually impaired users. This oversight has led to diminished cognitive effectiveness, disrupted workflows, and potential malfunctions [3][4][5]. A clear and concise icon is imperative for ensuring users accurately interpret its meaning and intended function [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, based on interface color research, Zhang, ZZ et al [ 26 ] discovered that by optimizing color semantics through Spearman rank correlation coefficient analysis, user satisfaction of smartphone interface icon color could be improved; Wu, TY et al [ 27 ] analyzed the visual elements of smart kitchen appliance interfaces for the elderly by combining perceptual engineering evaluation and experimental psychology to obtain the elderly’s preference for interface color information and graphics. Backhaus, N et al [ 28 ] and Wu, JF et al [ 29 ] established two control groups for the selection and identification of icons between young and old people, and between normal and cognitively impaired elderly people, respectively, in terms of interface icon ratio and icon selection, with results that showed that older persons prefer the skeuomorph version. It was concluded that the number of icons in one section of the interface design should not exceed 25, and the spacing between elements should be higher than 1/2 an icon for a modest number of icons [ 30 ].…”
Section: Introductionmentioning
confidence: 99%